EFISIENSI PASAR MODAL : PERBANDINGAN PADA DUA PERIODE YANG BERBEDA DALAM PASAR MODAL INDONESIA - Herman Legowo; Mas'ud Machfoedz (Faculty of Economics and Business, Universitas Gadjah Mada, 1998)
There are three grades in efficient capital market. They are: (1) weak form, (2) semi strong form, and (3) strong form. Weak form efficiency, the market is efficient in the weak sense if share prices fully reflect the information implied by all prior price movements.The purpose of this research is to know whether the stock price instataneously and fully reflect relevant historical information (weak form efficient capital market hypotesis). This means if someone trades stocks by using historical information, it will not earn abnormal return. In addition, this research is tests the assumption that capital market efficiency in the bullish condition is different from capital marketefficiency in the normal condition. The research is necessary for the reason that if slock price does not instantaneously and fully reflect relevant available informations, it will be able to mislead economic decisions.The focus of this research is on the monthly stock price (the share price at the end of the month) to 23 companies which went publicc before Januari 1989. The year of 1989 was capital market period in the bullish condition, while 1992 year period is capital market period in the normal condition.The hypothesis of this research is : (I) Jakarta Stock Exchange (JSX) is efficient, and (2) stock market (JSX) efficiency is the different after stock market condition to reach normal condition. The first hypothesis is to reach normal condition. The first hypothesis is to reach normal condition. The first hypothesis is tested by using probvalue which are base on randomnes test and serial correlation test. Randomnes test is used because one of the characteristics of the efficient market is that prices change randomly, while the serial corelation test is interrelated with the other characteristic of the efficient capital market, that the change of security prices has no corelation to each other. The statistical test, i.e. Wilcoxon 's signed rank test.From the statistical analysis of the data we find that hypothesis of this research, while serial corelation test failed to reject the second hypothesis. This research hypothesis that stock market efficiency in the bullish condition is different fromn stock market efficiency in the normal condition was fail to rejected. In other words, if the sample was representative of population, this reserch implicity stated that weak form capital market efficienyfor the year of1989 and 1992 are valid in Indonesia.The result of this research is in effect for 1989 and 1992 with monthly secondary-data get from the share price at the end of the month.